IMPEACHMENT PATTERN OF REGIONAL HEADS IN INDONESIA USING REGIONAL AUTONOMY PARADIGM APPROACH - Isnawati, Isnawati; Hidayati, Fatma; Setiawan, Adam (Jurnal Pembaharuan Hukum, 2024)
The issue of the dismissal of regional heads is often discussed in several expert circles because, if examined carefully, several juridical issues need to be comprehensively studied. The involvement of the central government in the process of dismissing regional heads is actually counterproductive to the paradigm of regional autonomy. Regional autonomy is oriented towards the independence of a region to manage its regional affairs. This paper discusses the pattern of impeachment of regional heads in Indonesia using the regional autonomy paradigm approach. The type of research used is doctrinal legal research (black letter law), which focuses on determining the law on certain issues. The results showed that there are four patterns of impeachment of regional heads and/or deputy regional heads. First, the process of dismissing a regional head involves the role of the Regional People’s Representative Council (DPRD) and the Central Government. Second, the dismissal involves the roles of the DPRD, Central Government, and Supreme Court. Third, the temporary dismissal of regional heads only involves the role of the Central Government. Fourth, dismissal occurs through the DPRD’s right of interpellation and investigation if evidence of criminal law is found. This shows that the pattern of dismissal of regional heads and/or deputy regional heads is centralized and even negates the spirit of regional autonomy because the DPRD does not have a role in dismissing regional heads. Apart from that, there are no clear provisions regarding public involvement in the impeachment process, which tends to have political nuances, making it neither accountable nor transparent.